ANALISIS TINGKAT KEPUASAN MAHASISWA PARIWISATA POLITEKNIK NEGERI BANYUWANGI TERHADAP KUALITAS JASA BIRO PERJALANAN WISATA INTERNAL DALAM PROGRAM PROJECT-BASED LEARNING - Okta Tri Wardatul Asvia; Eggi Savera; Berlian Dwi Yulianti; Lisa Afni Nursafitri; Masetya Mukti (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2026)
This study aims to analyze the satisfaction level of Tourism Department students at Politeknik Negeri Banyuwangi toward the quality of internal travel agency services used during Project Based Learning (PBL) activities in Bali. The research is motivated by the important role of travel agencies as the main facilitators in supporting project-based learning while simultaneously providing practical experience for students in managing tourism travel services. This study employed a quantitative approach using a survey method through questionnaires distributed to students who participated in the PBL activities. The sampling technique used was purposive sampling involving 60 respondents out of 180 students participating in the program. Instrument validity was tested using product moment correlation, while reliability testing used Cronbach’s Alpha, indicating that the instruments were valid and reliable. Data analysis was conducted using a Likert scale to measure student satisfaction toward core products and actual products of the travel agency services. The results indicate that accommodation obtained the highest satisfaction score with an average value of 3.32 categorized as “very satisfied”, followed by tour guide services with a score of 3.22 categorized as “satisfied”. Meanwhile, transportation and meal services still require improvement based on respondents’ feedback. In the actual product variable, both organizer quality and program design achieved an average score of 3.03 categorized as “satisfied”. The findings reveal that, overall, students were satisfied with the internal travel agency services used in PBL activities, although several aspects of the services still need improvement to achieve more optimal satisfaction.